The professional practice of architectural working drawings - Wakita, Osamu A.; Bakhoum, Nagy R.;Linde, Richard M. (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
The practical, comprehensive handbook for creating effective architectural drawings. In one beautifully illustrated volume, The Professional Practice of Architectural Working Drawings, Fourth Edition presents the complete range of skills, concepts, principles, and applications that are needed to create a full set of architectural working drawings. Chapters proceed logically through each stage of development, beginning with site and floor plans and progressing to building sections, elevations, and additional drawings.
Preface -- Part I. Professional foundations -- 1. The office -- 2. Standards, techniques, metrification, hand drafting, and computer-aided drafting -- 3. BIM, REvit, and human concerns -- 4. Sustainable/ Green Architecture -- 5. Construction materials and methods -- 6. Initial preparation phase for construction documents -- Part II. Document evolution -- 7. Site and grading plan -- 8. Floor plan -- 9. Foundation and roof plans, floor and roof framing systems -- 10. Building sections -- 11. Exterior and interior elevations -- 12. Schedules: door, window, and finish -- 13. Architectural details and vertical links (stairs/elevators) -- Part III. Case studies -- 14. Construction documents for a one-story, conventional wood-framed residence -- 15. Construction documents for a two-story, wood-framed residence with basement -- 16. Conceptual design and construction documents for a steel and masonry building (theater) -- 17. Madison steel building -- 18. Tenant improvements -- Index -- Appendix A. Survey of regional differences available online at www.wiley.com/go/wakita -- Appendix B: A uniform system for architectural working drawing available online at www.wiley,com/go/wakita.
Includes index.
Keywords: ARCHITECTURE -- DESIGNS AND PLANS -- WORKING DRAWINGS